2010
DOI: 10.1124/jpet.110.168294
|View full text |Cite
|
Sign up to set email alerts
|

Camptothecin Attenuates Cytochrome P450 3A4 Induction by Blocking the Activation of Human Pregnane X Receptor

Abstract: Differential regulation of drug-metabolizing enzymes (DMEs) is a common cause of adverse drug effects in cancer therapy. Due to the extremely important role of cytochrome P450 3A4 (CYP3A4) in drug metabolism and the dominant regulation of human pregnane X receptor (hPXR) on CYP3A4, finding inhibitors for hPXR could provide a unique tool to control drug efficacies in cancer therapy. Camptothecin (CPT) was demonstrated as a novel and potent inhibitor (IC 50 ϭ 0.58 M) of an hPXR-mediated transcriptional regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
2
37
0
1
Order By: Relevance
“…However, this treatment is not always successful and often unwanted pharmacological effects occur in cancer patients, such as unresponsiveness or toxicity. A common cause for these unpredictable effects is up and down regulation of drug transporters or drug-metabolizing enzymes such as cytochrome P450 (Harmsen et al, 2009;Chen et al, 2010). Of these enzymes, CYP3A4 is quantitatively the most important because it metabolizes more than 50% of all drugs and the majority of the currently prescribed anticancer drugs (Anzenbacher and Anzenbacherová, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, this treatment is not always successful and often unwanted pharmacological effects occur in cancer patients, such as unresponsiveness or toxicity. A common cause for these unpredictable effects is up and down regulation of drug transporters or drug-metabolizing enzymes such as cytochrome P450 (Harmsen et al, 2009;Chen et al, 2010). Of these enzymes, CYP3A4 is quantitatively the most important because it metabolizes more than 50% of all drugs and the majority of the currently prescribed anticancer drugs (Anzenbacher and Anzenbacherová, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has been described for ketoconazole [4], fluconazole [5], camptothecin [6] and a novel human immunodeficiency virus protease inhibitor [7] and has also been suggested for the diseasemodifying antirheumatic drug leflunomide [8]. In these studies, ketoconazole was shown to disrupt the binding of coregulators (including co-activators and co-repressors) to PXR in an agonist-dependent fashion [4].…”
Section: Introductionmentioning
confidence: 81%
“…Vast efforts have been made to develop analogs that address these drawbacks. Some of these analogs activate PXR, including irinotecan [101] and topotecan [102], which is in line with the fact that the ligand cavity is very flexible and may be able to accommodate structurally similar molecules in various orientations [103]. As a matter of fact, the agonist SR12813 occupies the ligand pocket in multiple orientations [104], but it is fixed in a single distinct position upon co-activator binding [105].…”
Section: Pxr As a Potential Target To Manage Drug-induced Liver Inmentioning
confidence: 99%